Analysis of Bonding Performance of Grouting Corrugated Pipes in Fabricated Bridge Structures. (23rd May 2022) - Yang, Sanqiang; Dai, Zeyu; Yang, Xiang; Zhou, Tong; Tang, Lanjun
Abstract : Prefabricated bridge structures are highly popularized due to their simple construction, economy, and environmental protection. Relying on the prefabricated prestressed concrete box girder bridge project of Rongwu Expressway Section 6, this research studies the structural mode of grouting bellows and the mechanical properties of joints under different design parameters. The laboratory test was carried out by adjusting the two design parameters of aperture ratio and material properties, and the test data of joint mechanical properties under the influence of different factors were analyzed with the help of grey relational theory. The result goes like this: when the size of the metal bellows is certain, the aperture ratio becomes smaller, the internal space of the specimen becomes smaller, the internal restraint is weakened, and the bonding performance of the reinforcement becomes worse. When D/d = 2.6, the performance of the specimen is better. Comparing the grouting materials with different characteristics, the performance of the metal bellows specimen increases with the enhancement of the properties of the grouting material, but as the aperture ratio becomes smaller, the influence of the grouting material on the performance of the specimen becomes weaker. The comprehensive analysis is carried out with the grey relational theory and the correlation degree of the influence of the two factors on the specimen, and the correlation degrees γ 1 = 0.66 and γ 2 = 0.67 are obtained. Both of them have a strong correlation with the performance of the specimen, and the degree of influence is roughly similar. Based on the engineering application requirements and related design requirements, the construction method of selecting 100 MPa high-strength grouting material which is higher than the general standard, 65 mm corrugated pipe, and 22 mm steel bar is finally put forward. This research relies on engineering theoretical and experimental studies, which provide important theoretical support and technical guarantee for the research on the joint structure of prefabricated structures.